A Prospective Analysis of the Burden of Multi-Drug-Resistant Pathogens in Acute Appendicitis and Their Implication for Clinical Management - Faruk Koca; Sara Fatima Faqar-Uz-Zaman; Claudia Reinheimer; Michael Hogardt; Volkhard A. J. Kempf; Paul Ziegler; Andreas A. Schnitzbauer; Armin Wiegering; Wolf Otto Bechstein; Patrizia Malkomes (Antibiotics)
Background/Objectives: Appendicitis caused by multi-drug-resistant pathogens is associated with significant postoperative morbidity. However, prospective data on the microbial spectrum and its clinical impact remain limited. Methods: Adults with acute appendicitis undergoing surgery between April 2022 and July 2023 were prospectively enrolled at a single university-affiliated institution. Bacterial cultures from appendiceal and rectal swabs were analyzed, and clinical outcomes were assessed. A telephone follow-up was conducted 30 days postoperatively. Results: A total of 105 patients were included. Multi-drug-resistant pathogens were identified in the appendiceal swabs of twenty-nine patients (27.6%), while six patients (5.7%) harbored multi-drug-resistant organisms (MDROs; according to the criteria of the CDC). Rectal swabs revealed MDROs in 11.4% of cases but showed a limited correlation with appendiceal samples, indicating that rectal colonization does not reliably predict the presence of MDROs in appendicitis. Patients with multi-drug-resistant infections had significantly higher postoperative complication rates (31% vs. 10.5%, p = 0.017), including more Clavien–Dindo grade 3 complications (17.2% vs. 2.6%, p = 0.007) and abdominal abscesses (10.3% vs. 1.3%, p = 0.03). These patients required more frequent postoperative antibiotic treatment (65.5% vs. 40.8%, p = 0.03) and therapy adjustments (37.9% vs. 15.8%, p = 0.02). Hospital stays were also prolonged in the multi-drug-resistant group (a median of 4 days and IQR of 5 days vs. a median of 3 days and IQR of 3 days; p = 0.03). Conclusions: Colonization with multi-drug-resistant pathogens in appendicitis is associated with worse clinical outcomes. The intraoperative microbiological analysis of appendiceal swabs in complicated cases may enable targeted antibiotic therapy, potentially shortening hospital stays, optimizing patient management and reducing healthcare costs.